2004
DOI: 10.1074/jbc.m313842200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Regulated Kinase/Mitogen Activated Protein Kinase Is Up-regulated in Pulmonary Emphysema and Mediates Matrix Metalloproteinase-1 Induction by Cigarette Smoke

Abstract: The interstitial collagenase matrix metalloproteinase-1 (MMP-1) is up-regulated in the lung during pulmonary emphysema. The mechanisms underlying this aberrant expression are poorly understood. Although cigarette smoking is the predominant cause of emphysema, only 15-20% of smokers develop the disease. To define the signaling pathways activated by smoke and to identify molecules responsible for emphysema-associated MMP-1 expression, we performed several in vitro and in vivo experiments. In this study, we showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
173
3
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(193 citation statements)
references
References 40 publications
15
173
3
2
Order By: Relevance
“…Moreover, immunohistochemistry on emphysematous lung tissue has shown that MMP-1 is expressed in epithelial cells, especially type II pneumocytes. Increased MMP-1 expression in the epithelial cells of smokers may result from a prolonged activation of the ERK mitogen-activated protein kinase pathway (Mercer et al, 2004). These data suggest that inflammatory cells may not be exclusively responsible for lung tissue destruction, but that MMP-1 expression in epithelial cells can cause emphysema .…”
Section: Neoplastic Diseasesmentioning
confidence: 76%
“…Moreover, immunohistochemistry on emphysematous lung tissue has shown that MMP-1 is expressed in epithelial cells, especially type II pneumocytes. Increased MMP-1 expression in the epithelial cells of smokers may result from a prolonged activation of the ERK mitogen-activated protein kinase pathway (Mercer et al, 2004). These data suggest that inflammatory cells may not be exclusively responsible for lung tissue destruction, but that MMP-1 expression in epithelial cells can cause emphysema .…”
Section: Neoplastic Diseasesmentioning
confidence: 76%
“…However, previous reports have also shown that MMP-1 is induced in NHBE cells exposed to cigarette (Imai et al, 2001;Maunders et al, 2007;Mercer et al, 2004). It is possible that proteins such as MMP-1 are expressed at levels that are sufficient to cause destruction to the lung by acting in their immediate surroundings but will be difficult to detect by conventional methods, such as Western blotting.…”
Section: Discussionmentioning
confidence: 93%
“…[33][34][35][36][37][38] We have suggested that EGR-1 can also stimulate HSP70 elevation in an ERK 1/2-dependent manner, which is thought to regulate cigarette smoke-induced inflammatory processes. 18 Here we provide the first evidence that EGR-1 could activate MAPK ERK 1/2 in a positive feedback manner through increasing Ras prenylation by promoting GGPPS transcription in lung epithelial cells during CSE challenge (Figure 6).…”
Section: Discussionmentioning
confidence: 99%